INCREASING EFL STUDENTS' DESCRIPTIVE WRITING SKILL BY USING VIRTUAL TECHNOLOGY ON ENGLISH LEARNING - Umar (Bajang Institute, 2021)
The present study attempts to examine the competence of descriptive writing skills of the Eighth Grade of Junior High School in the Sumbawa District. The study employed virtual technology as a teaching medium. The quantitative descriptive research design was applied to collect pre-test and post-test data. The tests were descriptive text writing. The effectiveness of the virtual technology was measured by comparing pre-test, post-test, and paired samples t-test. Based on the data analysis result, it is evident that the virtual technology was significant for the eighth grade of Junior High Schools Lopok in the Sumbawa District.